2040 [videorecording (DVD)] - Gameau, Damon; Gameau, Damon; Miller, Hugh; Marks, Bryony; Lazzaro, Eva; Gameau, Zoë (Giant Interactive ; Together Films, 2021)
Award-winning director Damon Gameau (That Sugar Film) embarks on a journey to explore what the future could look like by the year 2040 if the solutions already available to improve our planet were embraced. Structured as a letter to his daughter, Gameau blends documentary with dramatized sequences and high-end visual effects to create a vision of how these solutions could regenerate the world.